VEGETAL AGROBIODIVERSITY IN THE ECONOMIC DYNAMICS OF BULGARIA - Bran, Mariana; Vasilev, Kolyo; Kolev, Bojidar; Daniela Bran, Stefania (Economics of Agriculture, 2012)
In the context of the current world crisis and the global climatic changes, Bulgarian agricultural and rural food economy is based on the sustainable preservation and management of natural resources and biodiversity in compliance with the European research field. Biodiversity as a complex interaction on Terra comprises living organisms and social and economic systems to which such is connected. In economic point of view are of significance cultivated species liable for the assurance of the necessary food to the population. The agricultural production is performed both traditionally and conventionally, in agricultural units of varied types. Such removed sugar-beet from the list of cultivated species due to the high level of production expenses for setting up and maintenance, the non-stimulating prices offered by processors, the dropping of the price on the world market and the cheap imports of unrefined raw sugar. The structure of cultures is dominated by cereals due to the economic interest manifested not only by small-size exploitations. Their technical outfit and high costs to assure the inputs influence the yields per hectare.